The Third Dimension. On the Dichotomy Between Speech and Writing - Tomasin, Lorenzo (Frontiers in Communication, 2021)
This paper introduces a more complex and refined articulated view than the classic and simple dichotomy of linguistic production. According to the traditional doxa, what is linguistically articulated is either spoken or written. Forms of written language have previously been considered a secondary representation of spoken forms and, at least in the alphabetic system, the only properly linguistic form. I argue that there exists a third dimension of language, which is internal. This internal form is lexically, phonetically and grammatically articulated, without being spoken in a proper sense, but which can be seen as the pre-condition for both spoken and written production. In other words, linguistic production does not necessarily imply the presence of two interacting speakers (or writers/readers). Production can be seen as the simple effect of an internal activity, and can be described without reduction to spoken or written forms. A consideration of this third dimension in a systematic way could enrich and strengthen approaches to many types of texts and help to productively integrate the traditional schemes adopted in Sociolinguistics, Historical Linguistics, Philology, Literary Criticism, and Pragmatics.